Effect of Processing Parameters on Gelcasting Process for Mo/Cu Powders. Issue 3 (March 2018) - Bohua, Duan; Chengkang, Qi; Dezhi, Wang; Zhuangzhi, Wu; Zhen, Fu; Yasong, Zhang; Xing, Wan
Abstract : Abstract: A non-aqueous gelcasting system of 2-hydroxyethyl methacrylate (HEMA)-1, 6-hexanediol diacrylate (HDDA) was adopted to prepare concentrated slurry of Mo/Cu powders. The effects of dispersant dosage, monomer content and solid loading on rheological behavior of slurry were studied. The effects of processing parameters such as monomer content, monomer/cross-linker ratio, initiator dosage, and temperature on the gelation behavior and green bodies' flexural strength were studied. The results show that solid loading influences the viscosity of slurry the most, followed by dispersant dosage and monomer content. The flexural strength of green bodies is increased with the increasing of monomer content and the decreasing of monomer/cross-linker ratio, while the initiator dosage has a slightly effect. On the basis of them, the optimum processing parameters for Mo/Cu non-aqueous gelcasting are as follows: HEMA content is 25 vol%∼30 vol%, monomer/cross-linker ratio is 10:1∼15:1, initiator dosage is 1.5 vol%∼2.5 vol%, and gelation temperature is 60∼80 °C.